A search for flaring very-high-energy cosmic γ-ray sources with the L3+C muon spectrometer - Dova, María Teresa (2006)
The L3+C muon detector at the CERN electron–positron collider, LEP, is used for the detection of very-high-energy cosmic c-ray sources through the observation of muons of energies above 20, 30, 50 and 100 GeV. Daily or monthly excesses in the rate of single-muon events pointing to some particular direction in the sky are searched for. The periods from mid July to November 1999, and April to November 2000 are considered. Special attention is also given to a selection of known c-ray sources. No statistically significant excess is observed for any direction or any particular source.